2018
DOI: 10.5194/acp-2017-1182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling the impact of solar brightening on summer surface ozone over Europe between 1990 and 2010

Abstract: 10Surface solar radiation (SSR) observations have indicated an increasing trend in Europe since the mid-1980s, referred to as solar "brightening". In this study, we used the regional air quality model, CAMx (Comprehensive Air Quality Model with extensions) to simulate and quantify, with various sensitivity runs (where the year 2010 served as the base case), the effects of increased radiation on photolysis rates (PHOT1, PHOT2 and PHOT3 scenarios) and biogenic volatile organic compounds (BVOCs) emissions (BIO sc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…However, none of the models that participated in the exercise have explicitly accounted for such an interaction and the ERA-interim forcing data rely mainly on climatological aerosol profiles. On the other hand, recent sensitivity studies performed in Europe showed that such effects might be relatively small (Oikonomakis et al, 2018). Figure 16 and Figure 17 also show the relative trends in BSOA and ASOA concentrations for all the models that were able to provide twenty-one years of data.…”
Section: Meganv2mentioning
confidence: 95%
“…However, none of the models that participated in the exercise have explicitly accounted for such an interaction and the ERA-interim forcing data rely mainly on climatological aerosol profiles. On the other hand, recent sensitivity studies performed in Europe showed that such effects might be relatively small (Oikonomakis et al, 2018). Figure 16 and Figure 17 also show the relative trends in BSOA and ASOA concentrations for all the models that were able to provide twenty-one years of data.…”
Section: Meganv2mentioning
confidence: 95%